Technology engagement in enhancing memory functionality in elderly care centers - Feras Ali Mohammad Al-Habies; Mamdouh Baniah Lafee Al Zaben; Abdullah M.A Al-Tarawneh; Nagham Mohammad Abu Al-Basal; Hanadi Aldreabi; Omar Ismail Hamzeh Alorani; Hend Abdulaziz Alsulaiman (Journal of Education and Health Promotion)
Background: Studies on technology engagement among the elderly have shown that cognitive function is associated with technology engagement. However, the impact of technology engagement on elderly memory functionality has yet to be determined. The current study investigates the impact of technology engagement on memory functionality among elderly care centers in Jordan. Materials and Method: A descriptive longitudinal study of population consisted of 470 residents at the selected care centers aged 65 years and above from Amman, Jordan in 2024. The purposive sampling method was used in sampling the participants. A reciprocal 2-year longitudinal study of technology engagement and memory functionality. The data was collected quantitatively using “Everyday Technology Use, Episodic Memory, Executive function, Clock Drawing Test (CDT), and Cognitive Assessment” tools and qualitatively using semi-structured interviews. The data analyzed descriptively and inferentially using NVivo and SPSS 23.0. Results: The analyzes showed that technology engagement had longitudinal positive effects on cognitive function over 2 years. The results showed that reciprocally, greater use of technology was significantly associated with better memory performance in the following years, B (SE) =0.20, SE =0.02, P < .001. The lagged effect of technology use on executive function was significant across waves, B = .27, SE =.015, P < .001. However, the lagged effect of executive function on the use of technology was not significant, B = .00, SE =.01, P = .14. Conclusion: The study contributed to a clearer understanding of the impact of technology engagement on memory function.